Pengaruh Model Pembelajarann Inquiry berbasis Video Interaktif terhadap Hasil Belajar IPAS pada Siswa Kelas V Sekolah Dasar - Utari, Eka Amelia; Susiloningsih, Wahyu (Universitas Muhammadiyah Magelang, 2026)
This study aims to examine the effect of an inquiry-based learning model supported by interactive video on the topic “Light and Its Properties” on the IPAS learning outcomes of fifth-grade elementary school students. The background of this study is the low level of student achievement in IPAS, which is caused by the limited use of learning media and the suboptimal implementation of inquiry-based learning. Inquiry learning is a model that encourages students to actively discover knowledge through investigative processes under teacher guidance. By integrating interactive video defined as video that allows users to actively interact features student engagement and learning comprehension can be enhanced. The research method employed was quantitative with a quasi-experimental design, specifically the post-test only control group design. The research subjects consisted of two fifth-grade classes at SDN Tenggilis Mejoyo 1 Surabaya, totaling 52 students, with 26 students in the control class and 26 students in the experimental class. The research instrument was a test consisting of multiple-choice and essay questions that had been tested for validity and reliability. The results of data analysis indicated a significant difference in learning outcomes between students in the experimental and control classes. Significant effect on improving the IPAS learning outcomes of fifth-grade students.